Organ donation after euthanasia in a patient living with dementia: a landmark case report - van Dijk, Nathalie; Vliegen, Fabiënne; Ham, Angelique; de Jongh, Wim; Berkhout, Freek Jan; Blankevoort, Jeroen; ten Hoopen, Rankie; Bollen, Jan; van Mook, Walther (Frontiers in Dementia, 2023)
Background Organ donation after euthanasia (ODE) has been performed over 100 times in the Netherlands, primarily involving patients suffering from a neurodegenerative or psychiatric disease. In recent years, the number of euthanasia cases related to dementia has increased in the Netherlands, with some patients living with dementia expressing a wish for organ donation after euthanasia. Methods We describe a unique case of a 67-year-old female diagnosed with primary progressive aphasia as part of frontotemporal dementia who requested and underwent organ donation after euthanasia. Results The patient had expressed her explicit wishes for both euthanasia and organ donation, which were discussed with her family physician, the Euthanasia Expertise Center (EE), and an organ donation coordinator. The patient was informed that to proceed with ODE, she should still be capable of voicing a voluntary and well-considered request for organ donation. The legally required euthanasia assessment procedure was carefully completed before ODE. Multiple healthcare professionals assessed the patient's competence, voluntariness, and unbearable suffering. Thereafter the patient's ODE request was granted, and both lungs and kidneys were successfully donated and transplanted. Post hoc analysis confirmed that all due diligence criteria for euthanasia were met, and the patient's relatives received an anonymous letter of gratitude from one of the organ recipients. Conclusions This unique case demonstrates that ODE is feasible from medical, ethical, and legal perspectives in patients living with dementia. This case highlights several aspects essential to enable an ODE request by a patient living with dementia to be granted, such as the role of the physician performing euthanasia, the relevance of the decision-making capacity of the patient, the presence of an advance directive, and the involvement of and support by relatives and caregivers. However, several unresolved ethical issues surrounding ODE in patients with dementia, especially in patients with advanced stages of dementia, warrant further exploration, including the timing of discussing organ donation after the initial euthanasia request.